Implications of Waqf Land Management from the Perspectives of Positive Law and Islamic Law: A Case Study of Waqf Land in North Sumatra - Harahap, Abd. Rahman; Nasution, M. Yasir; Pagar, Pagar (SASI, 2023)
Introduction: Waqf is a sign of giving whose implementation is carried out by retaining (ownership) of origin (tahbisul ashli), then making the benefits generally accepted. Purposes of the Research: To find out about the management of waqf property in North Sumatra, especially the waqf land of Tengku Darwisyah in Serdang Bedagai according to positive law and Islamic law.Methods of the Research: This research is a qualitative study with a social history approach to Islamic law.Results of the Research: The management of the waqf land of Tengku Darwisyah is still far from expectations because it has not been managed perfectly and only has a traditional and consumptive nature, and there has been no good management. In addition, the trustee of the waqf of Tengku Darwisyah is passive and even fatalistic by allowing tenants to build permanent structures such as places of worship, sports halls (GOR), farms, and trading companies, which should be productive, and this policy is not based on any contract or agreement.